The Use of Yoga in the Treatment of PCOS - Przesór, Agnieszka; Medźwiedzka, Natalia (Quality in Sport, 2025)
Polycystic ovary syndrome (PCOS) is a complex and common endocrine disorder, and affects women of reproductive age. Symptoms include multiple ovarian cysts, hyperandrogenism (high levels of male hormones), and irregular menstrual cycles. PCOS is associated with a variety of health problems, including insulin resistance, obesity, hirsutism (excessive hair growth), and fertility problems. Lifestyle interventions and weight loss, if appropriate, remain the first-line treatment for women with PCOS. Regular physical activity is recommended for women with PCOS to maintain a healthy weight and cardiovascular fitness. Yoga is a system of exercises, called asanas, that originates from ancient India. Asana means “comfortable posture,” so any yoga posture is considered optimal for human well-being and balance. There are also more complicated asanas, especially for beginners, that can feel like they are taking away from one’s balance. In addition to asanas, breathing techniques known as pranayama are also very important in yoga. Practicing yoga is an excellent tool in improving the functioning of our entire body, both on the level of psyche and physis, which is why it is especially valuable for patients with PCOS. Aim of study: The purpose of this review is to demonstrate the beneficial effects of yoga on the body of women with PCOS. Materials and methods: This review was conducted by searching for scientific publications in PubMed and Google Scholar. The analysis included searching using the words: pcos, yoga pcos, yoga physical activity and then briefly summarizing their findings. Conclusions: The literature review and the presented results of clinical studies show that a holistic approach to PCOS treatment, including physical exercise in the form of yoga exercises, has a positive effect on the quality of life of patients.